2022
DOI: 10.31124/advance.19799821.v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Factors Related to Teacher Resilience during COVID-19

Abstract: <p>Teachers were surveyed across the United States between January and February 2021 (n=355). Participants were asked about learning modalities employed at their school as well as other factors related to COVID-19 mitigation, job satisfaction, teacher self-efficacy, burnout, teacher autonomy, and student access to resources.</p>

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…Teaching under these circumstances was not easy. It was especially difficult for those who were learning new technologies (Juan-Ignacio et al, 2021; Marshall, Shannon, & Love, 2022); recreating their lessons for a virtual format (Love & Marshall, 2022); teaching students in the classroom as well as those on Zoom simultaneously (Bartlett, 2022); or doing all of the above in the same school year.…”
mentioning
confidence: 99%
“…Teaching under these circumstances was not easy. It was especially difficult for those who were learning new technologies (Juan-Ignacio et al, 2021; Marshall, Shannon, & Love, 2022); recreating their lessons for a virtual format (Love & Marshall, 2022); teaching students in the classroom as well as those on Zoom simultaneously (Bartlett, 2022); or doing all of the above in the same school year.…”
mentioning
confidence: 99%
“…Finally, schools need to support teachers and recognize how demoralized teachers are at the moment. Almost three-fourths of teachers indicated that they considered leaving their job at the end of the 2021-2022 school year (Marshall et al, in press), a figure that was up sharply from the year prior (Marshall et al, 2022c), which was much greater than historical trends (Ingersoll, 2014;Papay et al, 2017). School leaders must take steps to provide appropriate resources to teachers and find ways to appropriately compensate teachers for the jobs they are completing (Mackenzie, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Compensation was found to be a significant factor for teacher morale in a number of studies (i.e., Mackenzie, 2007). Given that research conducted during the pandemic has found a relationship between morale and an intention to remain in the profession (Marshall et al, 2022c), developing a better understanding of teacher morale is important.…”
Section: Teacher Moralementioning
confidence: 99%
“…Between March 2020 and the conclusion of the 2021-2022 school year, teachers in the United States and around the world were asked to teach in ways that were outside of traditional methods, learn and use new technology, and navigate multiple learning modalities (sometimes simultaneously) -all while implementing strategies to mitigate the spread of the virus (Bartlett, 2022;Marshall, 2022). All of this exacerbated teacher burnout and attrition issues, making the execution of retention strategies in a field historically labeled as "high-stress" even more complex (Diliberti et al, 2021;Marshall et al, 2022a).…”
Section: Understanding Teacher Burnout Following Covid-19mentioning
confidence: 99%
“…In the past two years, several challenges and changes to traditional teaching approaches have been associated with increased teacher attrition rates (Marshall et al, 2022a;Marshall et al, 2022b;Zamarro et al, 2022). Research conducted early in the pandemic found that teachers had higher levels of burnout, anxiety, and workloads (Chan et al, 2021;.…”
Section: Understanding Teacher Burnout Following Covid-19mentioning
confidence: 99%